The Influence of the Use of Learning Media and Learning Motivation on Social Science Learning Outcomes - Nurdin; Rais, Rinovian; Sumadyo, Bambang; Diharjo, Darilah (Journal of Education Reseach and Evaluation, 2023)
Photographic image learning media is said to be able to arouse students' learning motivation so they can understand the teaching material better. Meanwhile, for computer learning media, students are asked to look at pictures to increase motivation in learning. This research aims to analyze the differences in social science learning outcomes using photographic image learning media and computer learning media for students with high motivation and low motivation. This research uses a quasi-experiment with a 2x2 factorial design. The learning material in the experiment is social science problems for grade 11, with a sample of 80 students who already have adequate initial knowledge. This study uses a two-way analysis of variance, and the Tukey test is used to test data analysis. The research results reveal an interaction effect between learning media and learning motivation on social science learning outcomes. Learning media using computers is better used in groups of students with high learning motivation, and learning media using photographic images is better used in groups of students with low learning motivation.